Banking the brain: Addressing the ethical challenges of a mental‐health biobank. (19th April 2013) - Amarasinghe, Myanthi; Tan, Hannah; Larkin, Samantha; Ruggeri, Barbara; Lobo, Sarah; Brittain, Philip; Broadbent, Matthew; Baggaley, Martin; Schumann, Gunter
Abstract : Mental health diagnoses are largely based on clinical observation and symptom reports, rather than biological evidence. A biobank that collects biological samples should allow the identification of disease mechanisms and more effective treatments.